Konsep, Dinamika, dan Gaya Kepemimpinan Kiai di Pesantren Salaf-Modern:: Studi Kasus PP. An-Nur 2 Malang - Edy Setiawan; Emilda Fibyani Agustin; Sultan Faiz Amrillah; Muhammad Zaironi (Jurnal Tinta, 2026)
This study investigates the construction of Kiai leadership in navigating the dualism of the educational system at the An-Nur 2 Malang Islamic Boarding School, which integrates the Salaf (traditional) curriculum with the Modern (formal) education system. This study aims to dissect the concept, dynamics of change, and typology of leadership styles applied in maintaining turats orthodoxy while responding to the demands of modernity. Through a qualitative case study approach, the study found that the concept of leadership at An-Nur 2 no longer relies solely on a single charismatic authority, but has metamorphosed into "Charismatic-Rational" leadership. The leadership dynamics are seen in the delegation of managerial authority to the pesantren bureaucratic structure without reducing the spiritual centrality of the Kiai. The leadership style applied is a hybrid between a paternalistic style in fostering the morals of students and a transformational style in developing infrastructure and educational curriculum. The implications of this study confirm that the success of Salaf-Modern Islamic Boarding Schools depends on the agility of the Kiai in their dual roles as guardians of tradition and system innovators.